Genome-wide analysis of growth-regulating factors (GRFs) in Triticum aestivum - Huang, Wendi; He, Yiqin; Yang, Lei; Lu, Chen; Zhu, Yongxing; Sun, Cai; Ma, Dongfang; Yin, Junliang (PeerJ, 2021)
The Growth-Regulating Factor (GRF) family encodes a type of plant-specific transcription factor (TF). GRF members play vital roles in plant development and stress response. Although GRF family genes have been investigated in a variety of plants, they remain largely unstudied in bread wheat (Triticum aestivum L.). The present study was conducted to comprehensively identify and characterize the T. aestivum GRF (TaGRF) gene family members. We identified 30 TaGRF genes, which were divided into four groups based on phylogenetic relationship. TaGRF members within the same subgroup shared similar motif composition and gene structure. Synteny analysis suggested that duplication was the dominant reason for family member expansion. Expression pattern profiling showed that most TaGRF genes were highly expressed in growing tissues, including shoot tip meristems, stigmas and ovaries, suggesting their key roles in wheat growth and development. Further qRT-PCR analysis revealed that all 14 tested TaGRFs were significantly differentially expressed in responding to drought or salt stresses, implying their additional involvement in stress tolerance of wheat. Our research lays a foundation for functional determination of TaGRFs, and will help to promote further scrutiny of their regulatory network in wheat development and stress response.
Keywords: GRF; Gene expression; Abiotic stress; Growing development; qRT-PCR